Current trends in the representation of physical processes in weather and climate models - Randall, David A. (David Allan), 1948- (New York, NY : Springer Berlin Heidelberg, 2018)
This book focuses on the development of physical parameterization over the last 2 to 3 decades and provides a roadmap for its future development. It covers important physical processes: convection, clouds, radiation, land- surface, and the orographic effect. The improvement of numerical models for predicting weather and climate at a variety of places and times has progressed globally. However, there are still several challenging areas, which need to be addressed with a better understanding of physical processes based on observations, and to subsequently be taken into account by means of improved parameterization. And this is all the more important since models are increasingly being used at higher horizontal and vertical resolutions. Encouraging debate on the cloud- resolving approach or the hybrid approach with parameterized convection and grid-scale cloud microphysics and its impact on models' intrinsic predictability, the book offers a motivating reference guide for all researchers whose work involves physical parameterization problems and numerical models
Includes bibliographical references.
Keywords: Weather forecasting; Climatology -- Mathematical models